Pengaruh Kondisi Lapangan terhadap Perancangan Menara Komunikasi Tipe Standar SST E-60 - Sumargo Syamsul Basri; Irwan I (Forum Teknik, 2006)
In the recent years, the communication sector has made a progressive development. The development is not only in the cornmunication technology, but also its supporting equipment. Communication tower is among the supporting equipments as a transmitter which is designed using steel material.At the design stage, companies that design communication tower, have one or few models that hqs been used. Among the communication towers that have been used is communication tower of SST(Self Supporting Tower) E-60 type with 60 m height. The preliminary model is designed with certain field conditions, and came into a question, what will occur if communication tower be built in different field conditions?In this Steady, analysis is conducted to SST E-60, if it can be built in all earthquake zone inIndonesia, can be put in oblique land or with different elevation, how big differential settlement is allowed to happen cmd how many extra antennas can be put on the tower structure. The result shows that commtmication tower of SST E-60 type can be used in all earthquake zone inIndonesia, can be built vith dffirent elevation, has a dffirential ,seltlement ntaxintwn of 2.5 cm, and can he put extra antenna as much as 26 antennas. Keywords: Communicalion tower, SST E-60, self  supporting tower, wilayah gempa (earth zone), tanah miring (oblique land), differential settlement, antena.